2022
DOI: 10.3389/fevo.2022.924248
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and gene-family dynamic analyses reveal gene expression pattern and evolution in toxin-producing tissues of Asiatic toad (Bufo gargarizans)

Abstract: Comprising a major clade of Anura, toads produce and secrete numerous toxins from both the parotoid glands behind their eyes and their dorsal skin. These toxins, made of various proteins and compounds, possess pharmacological potential to be repurposed to benefit human health. However, the detailed genetic regulation of toad toxin production is still poorly understood. A recent publication uncovering the genome of the representative Asiatic toad (Bufo gargarizans) provides a good reference to resolve this issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Comparative genomic research has identified specific substitutions that allow toxic amphibian species to effectively mitigate the effects of the sequestered toxins on their own tissues [94][95][96]. Skin transcriptomes have also proven to be a rich source for data mining and the identification of candidate toxins and antimicrobial peptides in various amphibians, including caecilians [97][98][99][100][101].…”
Section: Ecology and Evolutionmentioning
confidence: 99%
“…Comparative genomic research has identified specific substitutions that allow toxic amphibian species to effectively mitigate the effects of the sequestered toxins on their own tissues [94][95][96]. Skin transcriptomes have also proven to be a rich source for data mining and the identification of candidate toxins and antimicrobial peptides in various amphibians, including caecilians [97][98][99][100][101].…”
Section: Ecology and Evolutionmentioning
confidence: 99%